Refractory ventricular tachycardia caused by inflow cannula mechanical injury in a patient with left ventricular assist device: Catheter ablation and pathological findings. Issue 5 (11th May 2017) - Pedretti, Stefano; Cipriani, Manlio; Bonacina, Edgardo; Vargiu, Sara; Gil Ad, Vered; Frigerio, Maria; Lunati, Maurizio
Abstract: In patients with left ventricular assist device (LVAD), a minority of post‐operative ventricular tachycardias (VTs) is caused by contact between the inflow cannula and the endocardium. Currently, electrophysiologic characteristics and pathologic features of this condition are lacking. We report on a case of a successfully ablated mechanical VT. After VT recurrence, heart transplantation took place. Pathologic observations were consistent with direct tissue injury and inflammation, eventually contributing to persisting arrhythmias. Radiofrequency catheter ablation can be a safe and effective option to treat arrhythmias caused by inflow cannula interference in the short term, although a high recurrence rate is expected.